Association of Urinary Pentosidine Levels With the Risk of Fractures in Patients With Severe Osteoporosis: The Japanese Osteoporosis Intervention Trial‐05 (JOINT‐05). (31st August 2022) - Tanaka, Shiro; Saito, Mitsuru; Hagino, Hiroshi; Mori, Satoshi; Nakamura, Toshitaka; Ohta, Hiroaki; Sone, Teruki; Takahashi, Kaito; Mitomo, Yuji; Sugimoto, Toshitsugu; Soen, Satoshi; ,
ABSTRACT: Associations between urinary pentosidine, one of the advanced glycation end products in collagen, and the risk of fracture in patients with severe osteoporosis are unknown. In this study, we investigated whether the urinary pentosidine level is associated with the incidence of morphometric vertebral fracture and nonvertebral fracture using data of a randomized, controlled trial, JOINT‐05. JOINT‐05 enrolled Japanese women aged 75 years or older with primary osteoporosis. Patients were randomly assigned (1:1) to receive sequential therapy (teriparatide followed by alendronate) or monotherapy with alendronate for 120 weeks. Incidences of vertebral and nonvertebral fractures were assessed morphologically. During treatment, urinary levels of pentosidine and serum levels of bone turnover markers (osteocalcin, procollagen type I amino‐terminal propeptide, and tartrate‐resistant acid phosphatase 5b) were measured. A total of 967 patients with baseline pentosidine levels were included in the study. Of these, 137 had vertebral fractures, and 42 had nonvertebral fractures. The rate ratios for vertebral fracture for the second (30–39 pmol/mL), third (40–49 pmol/mL), and fourth quartile (≥50 pmol/mL) groups divided by pentosidine level compared with the first quartile (<30 pmol/mL) group were 1.65 (95% confidence interval [CI] 0.99–2.75, p  = 0.06), 1.51 (95% CI 0.87–2.61, p  = 0.14), and 1.69 (95% CI 1.01–2.83, p  = 0.05), respectively. The corresponding rate ratios for nonvertebral fracture were 3.07 (95% CI 0.88–10.70, p  = 0.08), 2.34 (95% CI 0.61–8.95, p  = 0.22), and 3.95 (95% CI 1.14–13.67, p  = 0.03), respectively. The association of the urinary pentosidine level with the incidence of nonvertebral fracture was the strongest among the biomarkers assessed in the study. In conclusion, the urinary pentosidine level was associated with the risk of fracture in patients with severe osteoporosis receiving teriparatide or alendronate. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.